A transient myelodysplastic/myeloproliferative neoplasm in a patient with cardio‐facio‐cutaneous syndrome and a germline BRAF mutation. Issue 10 (15th August 2013) - Sekiguchi, Kazuhito; Maeda, Tomoki; Suenobu, So‐ichi; Kunisaki, Nobutaka; Shimizu, Miki; Kiyota, Kyoko; Handa, Yo‐suke; Akiyoshi, Kensuke; Korematsu, Seigo; Aoki, Yoko; Matsubara, Yoichi; Izumi, Tatsuro
ABSTRACT A male infant, born at 32 weeks gestation by cesarean because of hydrops fetalis, presented with multiple anomalies, such as sparse and curly scalp hair, absent eyebrows, frontal bossing, an atrial septal defect, pulmonary artery stenosis, and whole myocardial thickening. He was clinically diagnosed with cardio‐facio‐cutaneous (CFC) syndrome, and was confirmed to have a germline V‐raf murine sarcoma viral oncogene homologue B1 (BRAF) c.721 A>C mutation. At 1 month of age, he presented with a transient myelodysplastic/myeloproliferative neoplasm (MDS/MPN), which improved within a month without the administration of antineoplastic agents. This is the first report of CFC syndrome with MDS/MPN. The coexistence of MDS/MPN may be related to this BRAF c.721 A>C mutation. © 2013 Wiley Periodicals, Inc.